Detection and abundance of SARS-CoV-2 in wastewater in Liechtenstein, and the estimation of prevalence and impact of the B.1.1.7 variant. (30th November 2021) - Markt, R.; Endler, L.; Amman, F.; Schedl, A.; Penz, T.; Büchel-Marxer, M.; Grünbacher, D.; Mayr, M.; Peer, E.; Pedrazzini, M.; Rauch, W.; Wagner, A. O.; et al.
Abstract: The new coronavirus 2 (SARS-CoV-2) is known to be also shed through feces, which makes wastewater-based surveillance possible, independent of symptomatic cases and unbiased by any testing strategies and frequencies. We investigated the entire population of the Principality of Liechtenstein with samples from the wastewater treatment plant Bendern (serving all 39, 000 inhabitants). Twenty-four-hour composite samples were taken once or twice a week over a period of 6 months from September 2020 to March 2021. Viral RNA was concentrated using the PEG centrifugation method followed by reverse transcription quantitative PCR. The aim of this research was to assess the suitability of SARS-CoV-2 fragments to relate the viral wastewater signal to the incidences and assess the impact of the emerging B.1.1.7. variant. The viral load in the wastewater peaked at almost 9 × 10 8 viral fragments per person equivalent (PE) and day on October 25, and showed a second peak on December 22 reaching a viral load of approximately 2 × 10 8 PE −1 d −1 . Individual testing showed a lag of 4 days and a distinct underestimation of cases at the first peak when testing frequency was low. The wastewater signal showed an immediate response to the implementation of non-pharmaceutical interventions. The new virus variant B.1.1.7. was first detected in wastewater on December 23, while it was first observed with individual testing on January 13, 2021. Further, our data indicate that the emergence of new virus variant may change the wastewater signal, probably due to different shedding patterns, which should be considered in future models. HIGHLIGHTS: Wastewater-based epidemiology covering an entire country (Liechtenstein). Lucrative lead of 4 days of SARS-CoV-2 gene copy numbers versus individual testing. Variant of concern B.1.1.7. detected in wastewater 2 weeks prior to individual testing. Variant of concern B.1.1.7. increased the ratio of wastewater signal per incidence.